Antimicrobial Activity of Olive Leaf Extract and Dental Gel against Some Pathogenic Fungi and Bacteria - Ghadeer H. Al-Jader (Journal of Global Pharma Technology, 2018)
The results of chemical detesters for some active substances in Olive leaf extract Revealed that contains Glycosides, Flavones, Saponine, Alkaloids and Turbines The statistical analysis of the results showed of the inhibitory effect of olive leaf extract on the growth of some pathogenic fungi, there are significant differences below the level of probability (P<0.05) between the inhibitory effectiveness of olive leaf extract of the studied species, compared with the standard antifungal (Itraconazole) used as control in the present study, table (2). The alcoholic extract of the olive leaf plant gave higher inhibition impact compared with the inhibitory effect of Itraconazole at the concentration 100% (Figure 1), the inhibitory effect of the extract at concentration of 100 % was (32, 35, 33, 36, 31, 35) mm to species (T. mentagrophytes, T. verrucosum, M. gypseum, M. audouinii, T. schoenleinii, M. canis) respectively, while was the inhibitory effect of Itraconazole (30, 31, 30, 34, 30, 30) mm respectively.Keywords: Denta gel, Olive leaves extravt, Antimicrobial Activity, Pathogenic bacteria.